Inclusion of Indigenous Tharu People in UNDP Supported Village Development Program: A case study of Benimanipur VDC, Nawaparasi, Western-Terai, Nepal - Tripathi, Damodar (Himalayan Journal of Sociology and Anthropology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> By using both qualitative and quantitative data generated from primary as well as secondary sources the study tries to find out to what extent the social mobilization approach of UNDP supported Village Development Program (VDP) was effective to include and able to empower the indigenous Tharu people. The socio-economic status of majority of Tharus was weak and limited by state policies since historical period and local power relations which played the pivotal role to result to exclude them from the mainstream of development. In macro level the social mobilization approach of VDP was strong to initiate the issue of inclusion to empower the marginalized people, but in local level it was weak to implement the policies efficiently and effectively regards to local diverse conditions and differentiated actors. The diversity in the village resulted in the different responses to the social mobilization program. Particularly the social mobilization process was generalized and limited by the local networks of power relation. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1496 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.54-72